The features of posttraumatic and associated sleep disorders in young War-affected women - Kohut Анна (Psychosomatic Medicine and General Practice, 2024)
The purpose of this study was to assess the specifics of PTSD symptom manifestations with accompanying sleep disturbances by identifying relationships between individual clusters of PTSD symptoms and indicators of sleep quality among the sample of younger women affected by military events. The study design is cross-sectional observational. Identical in basic parameters and socio-demographic indicators, the study population consisted of women aged from 18 to 45 years (M=23), (n=22). The study data included Ukrainian-language: demographic data, Patient Health Questionnaire-9 (PHQ-9), Generalized Anxiety Disorder Assessment-7 (GAD-7), PTSD Checklist for DSM-5 (PCL-5), Pittsburgh Sleep Quality Questionnaire (PSQQ), Toronto alexithymia scale (TAS-26) and Quality of Life Scale, edited by Prof. Chaban (CQLS). Statistical analysis including descriptive statistics and Pearson correlation was performed using SPSS Statistics 23.0 software. Significant relationships were identified and evaluated between the following indicators: individual clusters of PTSD symptoms with manifestations of anxiety-depressive symptoms and alexithymia, and the quality of life and sleep in young women with symptoms of post-traumatic disorders with accompanying sleep disorders due to military events. Consequently, significant relationships were established between the manifestations of individual clusters of PTSD symptoms and parameters of sleep quality with symptoms of anxiety, depression, alexithymia, and low quality of life. This may indicate the higher risk of development and degree of manifestation of symptoms of stress-related disorders with accompanying sleep disturbances in the future in individuals with corresponding indicators according to the results of the scales used.